Biosecurity in dentistry against COVID-19 - Alcocer Gamboa, Alessandra (2020)
The article presents various protection options and considerations to take into account in dental care in order to prevent and avoid contagion risks. Covid-19 is the virus that according to WHO reports affects the largest number of humans in recent years. months. During this time, dental emergencies and emergencies have been attended that lead to reviewing much stricter biosafety protocols. In Peru, dental care has already been restarted with biosafety protocols established by the Ministry of Health-Minsa, for safe dental care. The objective of this article is to review different protocols and compare the opinions of authors regarding the measures that must be taken into account in this new reality for optimal protection in dental care and for the control of the health of workers and patients. against a probable exposure to covid-19.